The heuristics debate - Kelman, Mark. (New York ; Oxford : Oxford University Press, 2011)
All of use heuristics - that is, we reach conclusions using shorthand cues without utilizing or analyzing all of the available information at hand. Here, Kelman takes a step back from the chaos of competing academic debates to consider the wealth of knowledge that a more expansive use of heuristics can open up.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Effectiveness and validity of law; Heuristic; Law -- Methodology